2004
DOI: 10.1152/ajplung.00271.2003
|View full text |Cite
|
Sign up to set email alerts
|

Increased pulmonary blood flow does not alter surfactant protein gene expression in lambs within the first week of life

Abstract: Neonates and infants with congenital heart disease with increased pulmonary blood flow suffer morbidity from poor oxygenation and decreased lung compliance. In a previous experiment involving 4-wk-old lambs with pulmonary hypertension secondary to increased pulmonary blood flow following an in utero placement of an aortopulmonary vascular graft, we found a decrease in surfactant protein (SP)-A gene expression as well as a decrease in SP-A and SP-B protein contents. To determine the timing of these changes, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Bhandari et al (4) found, in freshly isolated fetal type II cells, that exposure to S-nitroso-N-acetylpenicillamine (SNAP) and hyperoxia decreased surfactant protein mRNA levels. Ayad and Wong (2) In addition, in a lamb model of CHD with increased pulmonary blood flow and pressure, the interaction between NO and endothelin (ET)-1 signaling was found to mediate the dynamic changes in vascular tone following acute changes in fetal pulmonary blood flow (5-6, 47) and was also associated with a gradual decrease in surfactant protein gene expression (23,37).Although the effect of NO on surfactant has been studied previously, the model systems used whether in vivo or in vitro have made the interpretation of the effect of NO on surfactant protein gene expression difficult. In whole lung or mixed cell…”
mentioning
confidence: 99%
“…Bhandari et al (4) found, in freshly isolated fetal type II cells, that exposure to S-nitroso-N-acetylpenicillamine (SNAP) and hyperoxia decreased surfactant protein mRNA levels. Ayad and Wong (2) In addition, in a lamb model of CHD with increased pulmonary blood flow and pressure, the interaction between NO and endothelin (ET)-1 signaling was found to mediate the dynamic changes in vascular tone following acute changes in fetal pulmonary blood flow (5-6, 47) and was also associated with a gradual decrease in surfactant protein gene expression (23,37).Although the effect of NO on surfactant has been studied previously, the model systems used whether in vivo or in vitro have made the interpretation of the effect of NO on surfactant protein gene expression difficult. In whole lung or mixed cell…”
mentioning
confidence: 99%
“…With regard to mechanisms possibly involved in surfactant changes in the present SAVF model, and similar to previous studies (20,29), only assumptions can be proposed at present. Mechanical forces are known to modify alveolar epithelial cell phenotype as well as expression of surfactant proteins in vitro (18,19,21) and in vivo in normal (17,25,30,33) and hypoplastic lungs (8,9).…”
Section: Discussionmentioning
confidence: 60%
“…To our knowledge, the effects of increased pulmonary blood flow and/or pulmonary hypertension on the surfactant compartment were investigated previously in one model only that consisted in aortopulmonary shunt established at term in lamb fetuses (20,29), the lamb lungs being studied after spontaneous delivery, at 1 mo of life in a first step (20), then during the first postnatal week (29). Whereas no change was found in the first week, at 1 mo the authors reported a decrease in SP-A mRNA content to 61 Ϯ 8% of control value with a consistent decrease of SP-A to 50 Ϯ 12% of age-matched control value, and although SP-B mRNAs were not significantly changed, SP-B was found to be decreased to 74 Ϯ 25% of control value (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations